Middle and late latency ERP components discriminate between adults, typical children, and children with sensory processing disorders - Davies, Patricia L.; Chang, Wen-Pin; Gavin, William J. (Frontiers in Integrative Neuroscience, 2010)
This study examined whether combinations of middle latency sensory evoked potential components and late components, possibly indicative of cognitive processing, can discriminate between three sample groups; 18 adults (20 to 55 years), 25 typical children (5 to 10 years) and 28 children with sensory processing disorders (5 to 12 years). Electroencephalography (EEG) recordings were made while participants heard random presentations of two auditory stimuli (1k Hz and 3k Hz) each at two intensities (50 and 70 dB). Amplitude and latency measurements were obtained for the N1, P2, N2, and P3 components from the averaged event-related potential (ERP) for each of the 4 auditory stimuli. Discriminant analyses revealed two functions, one which described the relationship of the components on sensory processing deficit continuum and one which described the relationship of these components on a developmental continuum. Together, these two functions correctly classified 90.5% of the participants as to their group membership. These results are discussed in relation to neurodevelopmental theories.